2020
DOI: 10.1016/j.ydbio.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The developmental transcriptome for Lytechinus variegatus exhibits temporally punctuated gene expression changes

Abstract: Embryonic development is arguably the most complex process an organism undergoes during its lifetime, and understanding this complexity is best approached with a systems-level perspective. The sea urchin has become a highly valuable model organism for understanding developmental specification, morphogenesis, and evolution. As a non-chordate deuterostome, the sea urchin occupies an important evolutionary niche between protostomes and vertebrates. Lytechinus variegatus (Lv) is an Atlantic species that has been w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 162 publications
0
20
0
1
Order By: Relevance
“…To tackle these problems, we propose a transcriptomic "derivedness index" to address the degree of phenotypic changes observed in embryos, inherited from a common ancestor. Specifically, we compared the gene expression profiles of echinoderms (Tu et al, 2012;Li et al, 2018Li et al, , 2020Hogan et al, 2020) and chordates (Wang et al, 2013;Hu et al, 2017) to test whether echinoderms are more highly derived than chordates.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle these problems, we propose a transcriptomic "derivedness index" to address the degree of phenotypic changes observed in embryos, inherited from a common ancestor. Specifically, we compared the gene expression profiles of echinoderms (Tu et al, 2012;Li et al, 2018Li et al, , 2020Hogan et al, 2020) and chordates (Wang et al, 2013;Hu et al, 2017) to test whether echinoderms are more highly derived than chordates.…”
Section: Introductionmentioning
confidence: 99%
“…VHA is a housekeeping gene that is generally ubiquitously expressed (Sun-Wada and Wada, 2015). Each of the VHA subunits was identified in the Lytechinus variegatus (Lv) transcriptome (Hogan et al, 2020) and found to be expressed at all timepoints with variable expression levels (Fig. S1B; Table S1).…”
Section: Vha Activity Is Required For Normal Morphogenesis Of Sea Urchin Embryosmentioning
confidence: 99%
“…Each data point represents a minimum of two biologically independent replicates (each in triplicate, for a minimum of 6 measurements). ∆CT values were normalized to LvSetmar expression (Hogan et al, 2020); ∆∆CT values were determined by comparison to controls. Primer sequences used were previously reported (Gildor and Ben-Tabou de-Leon, 2015;Schatzberg et al, 2015), except those for LvAtp6v0a1 (forward: 5'-GCTCCTGCTCCTAGGGAGAT-3' and reverse: 5'-TCTCCATCGTCCATCTCATC-3').…”
Section: Molecular Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the present study investigated the long-term acid-base physiology of individuals of both species living in or out the plume of a cold volcanic CO2 seep (Levante Bay, Vulcano Island, Sicily), together with the impact on the mechanical properties of their skeleton and the expression of biomineralization-related genes. Based on a number of Omic and functional genomic studies performed on several sea urchin species (Consortium, 2006;Hogan et al, 2019;Livingston et al, 2006;Oliveri et al, 2008), four target genes (p19, msp130 sm50, and can) with known roles in the biomineralization process of both embryos and adults, and a housekeeping gene (z12), were selected for investigate the expression profiles in the samples above described. Orthologous genes of P. lividus and A. lixula, known or, here, preliminary identified and validated, provided the molecular tools of both species for setting-up species-specific Real-Time qPCR assays performing the analyses of gene expression here reported (for sequences identification and experimental setting see S01).…”
Section: Introductionmentioning
confidence: 99%